Changes in Functional Connectivity of Specific Cerebral Regions in Patients with Toothache: A Resting-State Functional Magnetic Resonance Imaging Study - Wu, Shi-Nan; Zhang, Meng-Yao; Shu, Hui-Ye; Liang, Rong-Bin; Ge, Qian-Ming; Pan, Yi-Cong; Zhang, Li-Juan; Li, Qiu-Yu; Shao, Yi (Disease Markers, 2020)
Objective. In order to further study the changes of cerebral functional connectivity in patients with toothache (TA), this study used the resting-state functional magnetic resonance imaging (rs-fMRI) technique and degree centrality (DC) analysis method. Methods. Eighteen TA patients (8 males, 10 females) and 18 healthy individuals of similar age, sex, and educational levels were recruited as healthy controls (HCs) to take part in the study, and all underwent rs-fMRI examination. And DC technology was used to compare the state of their cerebral spontaneous functional activity. In order to compare the average DC values of the TA group and HC group, we used independent two-sample t-test and receiver operating characteristic (ROC) curve to compare the difference of DC values between the two groups, so as to distinguish the accuracy of TA diagnosis. Finally, we also carry out Pearson’s linear regression analysis. Results. The TA group showed higher DC values in the right lingual gyrus (RLG), right precentral gyrus, and left middle temporal gyrus (LMTG) than HCs. Moreover, ROC curve analysis indicated that the area under the curve (AUC) of each cerebral region studied had high accuracy. In addition, linear analysis indicated that the DC values of the RLG were positively correlated with the Hospital Anxiety and Depression Scale (HADS) (r=0.844, p<0.001), and the DC values of the LMTG were positively correlated with the visual analogue scale (VAS) (r=0.723, p<0.001). Conclusion. TA generates abnormal changes in the intrinsic activity patterns of pain-related and vision-related areas of the cerebral cortex, which will be beneficial to reveal the underlying neuropathic mechanisms.